The association of donor and recipient sex on sepsis rates and hemoglobin increment among critically ill patients receiving red cell transfusions in a retrospective study - Wenhui Li; Yang Liu; Kayla J. Lucier; Nancy M. Heddle; Jason P. Acker (eJHaem)
Abstract Background Existing research presents conflicting results on the influence of blood donor sex on hemoglobin (Hb) change and transfusion‐associated infection and mortality in transfusion recipients. Aim This retrospective study explored the association between donor and recipient sex on hospital‐onset sepsis (HO‐sepsis) and Hb changes in critically ill patients receiving red blood cell (RBC) transfusions. Methods Data from 2010–2020 were extracted from an academic hospital's clinical database and a blood supplier's donor database. HO‐sepsis was determined based on the International Classification of Diseases and Related Health Problems 10th Revision (ICD‐10) diagnostic codes without requiring a microbiology test within the first 48 h of admission. Hb increments were determined by comparing the last Hb result in the 24‐h period prior to RBC unit issue and the first Hb result within 4–24 h after RBC unit issued for transfusion. Results 25,585 critically ill patients received one or more RBC transfusions; 3,410 were included in the HO‐sepsis and 3,487 in the Hb increment analysis. There was no significant differences in the HO‐sepsis rate among the four groups, but female recipients were more prone to HO‐sepsis than males (OR 1.48, p = 0.04). Multivariate analysis found that the number of RBC unit transfused (p = 0.001) and recipient age (p = 0.03), but not recipient sex (p = 0.63), were significant contributors to HO‐sepsis. Male blood was associated with higher Hb than female blood in female recipients (p = 0.007), but not in male recipients (p = 0.75). Variables such as donor Hb levels and recipient Hb level influenced Hb increments. Conclusion Blood donor sex was not associated with HO‐sepsis in critically ill patients receiving RBC transfusion. Male to female transfusions were associated with a higher Hb increment in recipients. Further exploration of the impact of sex mis‐matched transfusion on recipient outcomes is warranted.